Optimization and Stability Testing of a Nanostructured Lipid Carrier (NLC)-Based Emulgel System for Transdermal Delivery of Anti-Inflammatory Drugs - Muhammad Nurul Fadel; Emma Jayanti Besan; Dzukharian Munandar; Zola Efa Harnis; Indri Dwi Rahasasti (CV. Get Press Indonesia, 2026)
Nanostructured Lipid Carriers (NLC) are second-generation lipid nanoparticles composed of solid and liquid lipids that improve drug loading, stability, and controlled release. Incorporating NLC into an emulgel enhances transdermal drug delivery by improving skin permeation and prolonging drug release. This study aimed to optimize an NLC-based emulgel using Design of Experiment (DoE) and evaluate its physicochemical properties, drug release, skin permeation, and stability. Diclofenac sodium was selected as the model drug. NLC was prepared using melt-emulsification ultrasonication and optimized with a three-factor Box–Behnken design before incorporation into Carbopol 940 gel. Characterization included particle size, zeta potential, entrapment efficiency, viscosity, spreadability, and drug release analysis. The optimized formulation showed a particle size of 187.4 ± 5.2 nm, zeta potential of −32.6 ± 1.8 mV, and entrapment efficiency of 91.3 ± 2.1%. Drug release reached 85.6% within 24 hours following the Korsmeyer-Peppas model. Skin permeation was significantly higher than conventional gel, and the formulation remained stable for six months at 25°C/60% RH.